Bandwidth Enhancement: Correcting Magnitude and Phase Distortion in Wideband Piezoelectric Transducer Systems - Assous, Said; Rees, John; Lovell, Mike; Linnett, Laurie; Gunn, David (IntechOpen, 2011)
None